Pengembangan Buku Elektronik (E-Book) Pertolongan Pertama Gawat Darurat (PPGD) Risiko Cedera Pendakian Untuk UKM PA Gempa Unimuda Sorong - Andri Andriana Syatfle; Firman Firman; Indri Anugrah Ramadhani (Modem : Jurnal Informatika dan Sains Teknologi., 2025)
Andri Andriana Syatfle, Nim 148320719008 "DEVELOPMENT OF AN ELECTRONIC BOOK (E-BOOK) FOR EMERGENCY FIRST AID (PPGD) CLIMBING INJURY RISKS FOR UKM PA UNIMUDA SORONG EARTHQUAKE". Information Technology Education Study Program, Faculty of Exact Education, Muhammadiyah University of Education (UNIMUDA) Sorong. This research aims to develop learning media in the form of e-books which can be used as a varied learning media on Emergency First Aid (PPGD) material in the UNIMUDA Sorong Earthquake PA UKM. With this e-book learning media, Mapala Bumi members are more interested and active in learning. The research carried out by the author used the Addie model research and development (R&D) method in seven stages, namely potential and problems, data collection, product design, design validation, product design revision, product testing and product revision. Learning media in the form of e-books, the material that has been developed has been tested through a media validation questionnaire with an average assessment of 81.25% categorized as very feasible, the first material validation questionnaire with an average assessment of 97.5% categorized as very feasible, and a questionnaire second material validation with an average assessment of 75%, small group trials with an average assessment of 86.3% which were declared very feasible, and large group trials namely: large group trials which obtained an average assessment of 94 .5% is categorized as very feasible. This shows that the media is suitable for use in the learning process.